Light from below: canonical and theological implications of textual criticism - Adair, J. R. (Old Testament essays, 1998)
Since the late nineteenth century, textual criticism has often been called 'lower criticism', an unfortunate label with connotations of inferiority in comparison with the 'higher' critical methodologies like form or tradition criticism. However, textual criticism informs other areas of Biblical research, including questions of canon and theology. Textual differences among the witnesses to books like Daniel, Esther, Jeremiah, and Samuel provide evidence about the form of these books in certain times and places and among certain communities of believers, evidence that is relevant to modem discussions of canon. Textual criticism also provides evidence of ways in which the faithful of diverse backgrounds interpreted and at times even altered, the texts they were transmitting. Modem exegetes, theologians, and historians would do well to pay attention to the fruits of textual criticism.